SATU DEKADE, SEPARUH-JALAN PROSES DESENTRALISASI - Santoso, Dr Purwo (Jurnal Desentralisasi, 2010)
Decentralization process in the first decade had brought significant impacts, even though it was not satisfactory to arrive at final state of transformation process.The outcomes were in half way to go in achieving decentralization missions. New pattern of administration or government management had not yet beenestablished in order to facilitate the process. Development of public administration system had lost its strategic moment in directing spirit of autonomy within desirable framework. Upholding the missions would require political administration: political consensus to impose administrative instruments needed to safeguard policy implementation. Emphasize on political administration is important since strictly separating politics and administration would be impossible. Hence, meta-administrative evaluation is needed as essentially, decentralization requires fundamental reform of governance administration. In this context, it is reasonable to evaluate contribution of National Institute of Public Administration (LAN) in developing future decentralized governance administration-which is built on principles of autonomy.